Comparison of biotransformation and efficacy of aminoacetonitrile anthelmintics in vitro - Stuchliková, Lucie; Lecová, Lenka; Jirásko, Robert; Lamka, Jiří; Vokral, Ivan; Szotaková, Barbora; Holčapek, Michal; Skalová, Lenka (Wiley-Blackwell, 2016)
The present in vitro study was designed to test and compare anthelmintic activity, hepatotoxicity, and biotransformation of four selected aminoacetonitrile derivatives (AADs): monepantel (MOP, anthelmintic approved for the treatment), AAD-970, AAD-1154, and AAD-1336. Micro-agar larval development test, MTT test of cytotoxicity, and biotransformation study coupled with Ultra high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) technique were used for this purpose. Larvae of two Haemonchus contortus strains (drug susceptible and multi-drug resistant) and primary cultures of rat and ovine hepatocytes served as model systems. All AADs (including MOP) exhibited significant larvicidal effect in H. contortus susceptible as well as multi-resistant strains, much higher than those of reference anthelmintics thiabendazole and flubendazole. AAD-1154 provides the best results for most tested parameters among all AADs in this study. The cytotoxicity test showed that all AADs can be considered as nontoxic for hepatocytes. In the biotransformation study, Phase I and Phase II metabolites of AADs were identified and schemes of possible metabolic pathways in ovine hepatocytes were proposed. Biotransformation of MOP was much more extensive than biotransformation of other AADs. Based on obtained results, AAD-1154 and AAD-1336 can be considered as promising candidates for further in vivo testing.
In vitro porovnaní biotransformace a efektivity aminoacetoniritrilových anthelmintik
Keywords: monepantel; drug metabolism; micro-agar larval development test; hepatocytes; structure-metabolism relationships; anthelmintika; UHPLC-MS/MS; biotransformace